2010
DOI: 10.1371/journal.pone.0010579
|View full text |Cite
|
Sign up to set email alerts
|

Fear Conditioned Discrimination of Frequency Modulated Sweeps within Species-Specific Calls of Mustached Bats

Abstract: Social and echolocation vocalizations of bats contain different patterns of frequency modulations. An adult bat's ability to discriminate between various FM parameters, however, is not well established. Using changes in heart rate (HR) as a quantitative measure of associative learning, we demonstrate that mustached bats (Pteronotus parnellii) can be fear conditioned to linear frequency modulated (FM) sweeps typically centered at their acoustic fovea (∼60 kHz). We also show that HR is sensitive to a change in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
2
10
0
Order By: Relevance
“…Listening to fast amplitude modulated vocalizations boosts the bats' heart rate. As mentioned in the preceding text, acoustic stimulation is known to increase the bats' HR 31,49 . This effect was also visible in our data, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Listening to fast amplitude modulated vocalizations boosts the bats' heart rate. As mentioned in the preceding text, acoustic stimulation is known to increase the bats' HR 31,49 . This effect was also visible in our data, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…To determine whether bats could actually perceive fast amplitude fluctuations at 1.7 kHz we measured the heart rate (HR) response of awake animals while they listened to sequences of natural fAMVs and their demodulated versions. Previous studies have shown that the bats' HR increases when the animals are subject to fear conditioning, when they listen to aggression (versus non-aggression) calls, or after electric stimulation of the amygdala 31,48,49 . We thus reasoned that the HR could be a useful indicator of autonomic changes driven by the presence of fast amplitude modulations in the sounds.…”
Section: Resultsmentioning
confidence: 99%
“…Since many simple syllabic calls consist of relatively simple spectrotemporal elements, the patterns themselves together with their parameters, e.g., the slope of an upward vs. downward FM, the rate of an SFM, and the bandwidth of a noise burst may convey meaningful information within a call (Morton 1982(Morton , 1977 even when other important components of the social context are absent. Activity within the BLA was recently shown to be sensitive to fearconditioned discrimination of the direction of an FM (Ma et al 2010). Similarly, the ratio of harmonics within a CF call type may also represent a meaningful feature of a call type.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the LN also receives weak to moderate direct projections from the primary auditory cortex (AC) (Budinger et al 2008;Fitzpatrick et al 1998). Furthermore, BLA receives afferents carrying information about intrinsically aversive and rewarding stimuli (Lanuza et al 2004;Loughlin and Fallon 1983;McDonald 1998), which can be associated with environmental sounds as well as acoustic features within calls through experimental conditioning (Ma et al 2010) or natural experience. The amygdala's role in aversive and appetitive conditioning is well established (Everitt et al 2000;Maren and Quirk 2004;Salzman et al 2007).…”
mentioning
confidence: 99%
“…To determine whether bats could actually perceive fast periodicities (or low pitch, see preceding text) we measured the heart rate (HR) response of awake animals while they listened to sequences of natural FPVs and their computer demodulated versions. Previous studies have shown that the bats' HR increases when the animals are subject to fear conditioning, when they listen to aggression (versus nonaggression) calls, or after electric stimulation of the amygdala 38,57,58 . We thus reasoned that heart rate could be a useful indicator of autonomic changes driven by the presence of fast periodicities in the sounds.…”
Section: Listening To Fast Periodic Vocalizations Boosts the Bats' Hementioning
confidence: 99%